Study of Training Programme for Junior Cooperative Personnel and Member Education - Programme Evaluation Organisation Planning Commission (Programme Evaluation Organisation Planning Commission Government of India, 1970)
This summary reviews the findings of the Programme Evaluation Organisation’s assessment of training programmes for junior cooperative personnel and the Member Education Programme conducted during 1967–68. Covering multiple states, the evaluation examines the adequacy, quality, and impact of training on the functioning of cooperative societies. While the programmes contributed to improved awareness of cooperative principles and strengthened capacity in some regions, significant weaknesses were identified, including underutilized training institutes, inconsistent course structures, limited practical exposure, weak supervision, and inadequate follow-up mechanisms. The Member Education Programme faced additional challenges such as poor coordination, irregular funding, low participation, and insufficient teaching materials. The report recommends curriculum revision, stronger administrative frameworks, improved incentives, and systematic follow-up to enhance the effectiveness and sustainability of cooperative training and education, thereby supporting the long-term development of India’s cooperative sector.
Programme Evaluation Organisation Planning Commission Government of India 1969
Programme Evaluation Organisation Planning Commission Government of India 1969
Keywords: Cooperative Training Programmes; Junior Cooperative Personnel; Member Education Programme; Programme Evaluation Organisation; Cooperative Institutions; Training Effectiveness; Curriculum Development; Administrative Coordination; In-Service Training; Capacity Building; Cooperative Governance; Rural Development